Effect of microchannel on combined impingement and film cooling of a concave surface. (July 2021) - Jaiswal, Ajay Kumar; Mahapatra, Pallab Sinha; Prasad, Bhamidi V.S.S.S.
Abstract: In this work, a micro-channel-based wall cooling approach is investigated. The cooling efficiency of curved surfaces is determined by employing a computational study for conjugate heat transfer. A semi-circular curved body depicting the turbine blade leading edge, with a microchannel placed in the solid wall of the body and three rows of film holes, is considered for the study. The film holes are positioned along a stagnation line and either side of the stagnation line at an angle of 25 o . The steady-state solver with a realizable k-ε turbulence model is used to study the heat transfer results for film cooling in a 3D geometry. Simulations were carried out, and subsequently, parametric analysis was performed to observe the effect of varying blowing ratio and temperature ratio. The temperature distribution is observed to be more uniform due to the presence of the microchannel, resulting in a lesser thermal gradient on the curved surface. It is also noted that overall effectiveness increases with the blowing ratio. The maximum increase in overall effectiveness due to placing the microchannel is found to be 16% for the blowing ratio of three.